1992
DOI: 10.1080/01688639208402854
|View full text |Cite
|
Sign up to set email alerts
|

Specificity in the correlation of verbal memory and hippocampal neuron loss: Dissociation of memory, language, and verbal intellectual ability

Abstract: Fifty-nine patients with temporal-lobe epilepsy (28 left, 31 right) completed the Boston Naming Test (BNT), verbal subtests of the Wechsler Adult Intelligence Scale-Revised, and the Logical Memory Subtest of the Wechsler Memory Scale (WMS) before surgery. Performances by patients with left temporal seizure foci were significantly more impaired than those of patients with right seizure foci on the WMS Logical Memory subtest and the BNT. After surgical removal of the mesial temporal lobe structures, two blinded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
92
1
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(102 citation statements)
references
References 12 publications
8
92
1
1
Order By: Relevance
“…In patients with left MTLE, preoperative verbal memory deficit has been correlated with cell loss in CA3 (73). In many patients, the memory deficit affects both visual and verbal function, further support for the emerging concept of MTLE as a bilateral process.…”
Section: Developmental Acquired Medial Temporal Lobe Epilepsy Localmentioning
confidence: 68%
“…In patients with left MTLE, preoperative verbal memory deficit has been correlated with cell loss in CA3 (73). In many patients, the memory deficit affects both visual and verbal function, further support for the emerging concept of MTLE as a bilateral process.…”
Section: Developmental Acquired Medial Temporal Lobe Epilepsy Localmentioning
confidence: 68%
“…Furthermore, these findings may have relevance for pre-post surgical outcome in cognition. The focus of much of the surgical outcome literature has emphasized the integrity of the resected hippocampus for memory outcome (Chelune, 1995;Sass et al, 1992). Our findings suggest that cognitive variability in surgical outcome may also be related to thalamic integrity before and0or after surgery.…”
Section: Cognitive Functioningmentioning
confidence: 74%
“…However, in patients with left TLE, Lencz et al (36) reported a significant correlation between MRI estimates of lesion size in the left hippocampus and the Wechsler logical memory scores, which assess recall abilities. Likewise, Rausch and Babb (37) and Sass et al (38) reported a significant correlation between the Wechsler logical memory scores and the neuron density in the hippocampus in their histologic specimens, suggesting that hippocampal function may be involved in recall. Hermann et al (39) found that patients with mesial TLE were more impaired on both recall and learning tests than were patients without mesial TLE.…”
Section: Discussionmentioning
confidence: 89%